Privilege in the Delivery Room? Race, Class, and the Realization of Natural Birth Preferences, 2002–2013. (24th April 2020) - Johnson, Katherine M; Simon, Richard M
Abstract: We expand prior research on the sociology of birth by testing race and class effects on women's capacity to realize their childbirth preferences in hospital settings. Drawing on data from the U.S. Listening to Mothers survey, we use Poisson regression and logistic regression to examine the extent to which women's preferences are associated with actual experiences of medical intervention during perinatal care. We find that 1) less privileged women were significantly less likely to have certain interventions and had fewer interventions overall; but 2) less privileged women with natural birth preferences were significantly more likely to have certain medical interventions, compared to their race/class privileged counterparts. Thus, less privileged women simultaneously receive less and more childbirth interventions—both of which appear to be out of sync with their birthing preferences. Our results support previous research which has found race and social class inequities in medical treatment, which we interpret here as "privilege in the delivery room."